2013
DOI: 10.1007/s12603-013-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

“It could probably help someone else but not me”: A feasibility study of a snack programme offered to meals on wheels clients

Abstract: Objectives Community-based services, such as Meals on Wheels (MOW), allow older adults to remain in their homes for as long as possible. Many MOW recipients experience decreased appetite that limits intake at mealtimes. This pilot study aimed to determine the feasibility of providing high protein high energy snacks to improve nutrient intakes of MOW clients in a regional centre of New South Wales, Australia.Participants A convenience sample of 12 MOW clients.Intervention Participants received snacks five times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…MOW services have been shown to be effective in improving older adults’ nutritional status, and offering a good alternative for older adults who have limited ability to cook and prepare meals . Charlton et al . reported increased energy and protein intakes as well as an improved MNA score with MOW clients after four weeks of receiving nutrient‐dense snacks provided through the existing service.…”
Section: Discussionmentioning
confidence: 99%
“…MOW services have been shown to be effective in improving older adults’ nutritional status, and offering a good alternative for older adults who have limited ability to cook and prepare meals . Charlton et al . reported increased energy and protein intakes as well as an improved MNA score with MOW clients after four weeks of receiving nutrient‐dense snacks provided through the existing service.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings relating to eating environments 14-17 and quality improvement efforts [18][19][20] indicate congruence with these data, suggesting that a number of common challenges to nutritional care are experienced in health care. The frameworks of behaviour and implementation (e.g.…”
Section: Discussionmentioning
confidence: 56%
“…also report nurses’ challenges in encouraging patients to consume ONS. Elderly clients’ lack of receptiveness of snacks has also been attributed to their misconceptions about nutritional value of these items, their risk of malnutrition and its implications …”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies included in this review reported on a non-randomized intervention involving home-delivered meals (73, 74,75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85). Most of these involved tweaking or adding something different to existing home-delivered meals programs; these included: adding snacks (73), allowing food choices (74), receiving nutrition education (75), receiving meals post-hospital discharge (76, 78), adding breakfast (79), providing “heart healthy” meals and education (81), adding more meals and snacks (80), taking homebound older adults out to eat (82), adding dietary supplements (84), and providing frozen meals (85).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these involved tweaking or adding something different to existing home-delivered meals programs; these included: adding snacks (73), allowing food choices (74), receiving nutrition education (75), receiving meals post-hospital discharge (76, 78), adding breakfast (79), providing “heart healthy” meals and education (81), adding more meals and snacks (80), taking homebound older adults out to eat (82), adding dietary supplements (84), and providing frozen meals (85). Some studies were single group designs, while others had a comparison group.…”
Section: Resultsmentioning
confidence: 99%